2019
DOI: 10.1007/s40519-019-00809-2
|View full text |Cite
|
Sign up to set email alerts
|

What are people’s experiences of orthorexia nervosa? A qualitative study of online blogs

Abstract: Purpose Orthorexia nervosa (ON) is a proposed new eating disorder, used to describe a pathological obsession with healthy or 'clean' eating. Although some quantitative research has been carried out in ON, very little qualitative work has been published to date to explore individual experiences of ON. Thus, this study aimed to explore individuals' personal experiences of ON, as described in online blogs. Methods Fifteen women bloggers, who self-identified as having ON, consented for their blog entries to be ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Individuals with high ON tendencies had more difficulties identifying and accepting their feelings, and resisting impulses, engaging in goal-directed behaviors and finding the right strategies when upset compared to people with low ON tendencies. It has been hypothesized that ON behavior can be considered as a coping strategy in order to feel 'perfect' and in control [57] in these participants who have poor emotion regulation abilities [56]. It is possible that people with ON tendencies tend to perceive themselves to be more 'out of control' when experiencing negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high ON tendencies had more difficulties identifying and accepting their feelings, and resisting impulses, engaging in goal-directed behaviors and finding the right strategies when upset compared to people with low ON tendencies. It has been hypothesized that ON behavior can be considered as a coping strategy in order to feel 'perfect' and in control [57] in these participants who have poor emotion regulation abilities [56]. It is possible that people with ON tendencies tend to perceive themselves to be more 'out of control' when experiencing negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to the impulse subscale, which specifically looks at feeling out of control, many papers have indeed found that individuals with AN and BN show greater difficulties with controlling their behaviour during times of emotional distress compared with control groups [10,56,57]. Moreover, in our recent qualitative work exploring women's experiences of ON as described in their online blogs [42], restrictive dietary rules around healthy eating were described as a coping strategy to feel 'perfect' and in control. Exercise and food rules were described as serving the same purpose; increasing levels of perceived control, regardless of which food/ exercise rule was being adhered to.…”
Section: Emotion Regulationmentioning
confidence: 95%
“…While very little work has been conducted in ON, similar mechanisms may be in place. Indeed, in a recent qualitative study of 15 women bloggers who self-identified as having ON [42], restrictive dietary rules around healthy eating was described as a coping strategy in order to feel in control.…”
Section: Emotionsmentioning
confidence: 99%
“…Notably, very few participants identified weight loss or calorie reduction as key themes in their definition of “clean” eating, and although “clean” eating was frequently defined using language of dietary restriction, few respondents offered restrictive dietary behaviors as a potential harmful consequence of following “clean” diets. In a recent analysis of women bloggers’ experiences with orthorexia nervosa, participants reported that their diets were initially motivated by health problems (such as digestive issues) and a desire to be healthy, but that social influences (such as social comparisons of “healthiness”, and praise for pursuing “healthy” behaviors) and lack of awareness fueled their difficulties [ 22 ]. These data suggest that weight loss is likely not a defining feature for those who may eventually go on to pursue “clean” diets in an unhealthy manner, and that further research is needed to identify pathways that tip the balance from healthy to unhealthy pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet recognized as a standalone diagnosis, research suggests that orthorexia nervosa (ON) reflects an unhealthy preoccupation with healthy eating, one associated with substantial distress and functional impairment mirroring eating disorder psychopathology [ 18 , 19 ]. Moreover, the National Eating Disorder Association suggests that the “clean” eating trend may be associated with ON [ 20 ], and scholars often describe ON as an extreme variant of “clean” eating (e.g., [ 6 , 21 , 22 ]). Thus, “clean” eating may involve excessive dietary restriction resembling an eating disorder [ 23 ] and thereby increase risk for nutritional deficiencies [ 24 ].…”
Section: Introductionmentioning
confidence: 99%